ANALISIS BEBAN KERJA FISIK DAN PSIKIS DENGAN STRES KERJA PADA PEKERJA INDUSTRI PERTEKSTILAN DI BOYOLALI - , Wartini; , Prof. Dr. dr. Soebijanto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The work plays an important role for human lives. Work can provide satisfaction and challenge, can also be nuisance and threat. Working conditions, working organization design and unsuitable working capacity, such as speed and excessive workload is another factor that can be health problems caused by work. Factors of occupational health problems are not only physical factors but also with the psychological factors. Textile company X weaving section of environmental conditions that include light, work climate, and noise are not eligible. Physical and psychological workloads as well as physical working conditions that exceed the capacity of workers to influence the early fatigue will affect workers and job stress. Objective: To analyze the relationship of physical and psychological workload on job stress. Methods: The study used crossectional design with purposive sampling technique, data collection with interviews. Data collected was analyzed using correlation productmoment Pearson and regression. Results: There was no relationship between physical and mental workload with job stress. And there are no significans influence between physical and psychological workload together with job stress with contribution 3.9% to job stress on workers PT. X in Boyolali with influence contribution physichological workload 3.8% and physical workload 0.01%. Conclusions: there are not relationship between physical and psychological workload with job stress in Compani X Boyolali with contribution influence physichological workload more dominated than physical workload.